Analisis Perencanaan Kebijakan Jaminan Kesehatan Nasional dari Aspek Kepesertaan di Kementerian PPN/Bappenas - Oldistra, Feby; Machdum, Sari Viciawati (Jurnal Ilmu Kesejahteraan Sosial, 2020)
National Health Insurance (JKN) is one of the policies to support the implementation of social development programs in Indonesia. This is in accordance with the mandate of the 1945 Constitution, where the state provided social protection to achieve social justice. One of the determining factors for the success of the JKN program participation aspect. The SJSN Law of 2004 binds citizens to participate in this program without exception. JKN was first implemented in 2014 with coverage target is 95% of population until 2019. But in its development, up to 2020 the coverage of membership is 82.7%. This study aims to determine the dynamics in JKN program policy planning from the aspect of participation. This research used a qualitative method to analyse the dynamics of policy planning from stakeholders related to JKN in the Bappenas. Researchers conducted in-depth interviews with relevant officials in Bappenas and do some documentation studies. Documentation study data sourced from various planning documents from 2014 to 2019. The results showed that there were very optimistic targets related to participation, this target directly affected the quality of the JKN program, one of which was the current deficit condition. It is necessary to re-calculate the Universal Health Coverage target in Indonesia. Some obstacles that occur include differences in understanding of the program, institutional and funding problems, inconsistencies of participants and data.